Biological potential and therapeutic benefit of Chrysosplenetin: An Applications of polymethoxylated flavonoid in medicine from natural sources - Dinesh Kumar Patel (Elsevier, 2022)
Herbal medicines contain single herb or many herbal ingredients derived from the plant and their byproducts. The beneficial effects of medicinal plants in the healthcare system are mainly due to the presence of secondary metabolites which have numerous biological applications in medicine. Chrysosplenetin is a polymethoxylated flavonoid class phytochemical found to be present in Artemisia annua L. and Dracocephalum heterophyllum Benth. Scientific research data of chrysosplenetin has been collected from various literature databases in the present work and analyzed for their medicinal properties and pharmacological activities. Medicinal importance and pharmacological activity data of chrysosplenetin has been collected from Google, Science Direct, PubMed, and Scopus and analyzed in the present work to know the therapeutic benefit of chrysosplenetin. However, the analytical data of chrysosplenetin has been also collected and analyzed in the present work to know the importance of modern analytical techniques in the separation, isolation, and identification of chrysosplenetin. Scientific data analysis of collected research work from various literature databases revealed the biological importance of chrysosplenetin in medicine. Pharmacological data of chrysosplenetin revealed the anti-malarial, antiproliferative, and antibacterial effect of chrysosplenetin. Chrysosplenetin has a significant effect on bone loss, enterovirus 71, trichomoniasis, tyrosinase enzyme, multidrug resistance, inflammatory, and neurological disorders. Pharmacokinetic parameters of chrysosplenetin have been also studied in the present work. Literature data analysis signified the potential role of different analytical techniques in medicine for their isolation, separation, and quantification. Scientific data analysis of the collected data of chrysosplenetin in the present work signified the therapeutic benefit of chrysosplenetin in medicine for the treatment of numerous diseases and associated complications.